HOME SECURITY SYSTEM BASED ON ARDUINO UNO USING SMS - yudi Ahsana Maswa; Lalu Puji Indra kharisma; Arief Taufikurrahman; Sri Andani (JATISKOM : Jurnal Aplikasi Teknologi Informasi dan Sains Komputer, 2024)
Security is a crucial aspect for everyone. Homes that are frequently left unattended by their owners can become targets for thieves to carry out their actions. Therefore, an effective home security system is needed to enable homeowners to receive information if their house is broken into by a thief. The author has developed a home security system utilizing technology with an Infrared sensor and GSM module as an SMS alert information system, where all components are processed in an Arduino Uno microcontroller. The research methodology used includes several stages: data collection (literature review, observation, and experimentation) and software development using the prototype method (communication, quick planning, quick design modeling, prototype construction, deployment delivery, and feedback). The home security system works by using sensors placed at entry points, such as doors. This system automatically sends an SMS to the homeowner's mobile phone, regardless of their location.